2009
DOI: 10.1007/s10646-009-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage effects in the copepod Tigriopus japonicus Mori experimentally exposed to nickel

Abstract: Tigriopus japonicus Mori has been recognized as a good model for toxicological testing of marine pollutants. Recently, a large number of genes have been identified from this copepod, and their mRNA expression has been studied independently against exposure to marine pollutants; however, biochemical-response information is relatively scarce. The response of T. japonicus to nickel (Ni) additions was examined under laboratory-controlled conditions in 12 days exposure. Superoxide dismutase (SOD), glutathione perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 79 publications
(84 reference statements)
3
14
0
Order By: Relevance
“…**p < 0.01, compared with the control group or lesions [18][19][20][21][22]. Some studies have reported that NiCl 2 can decrease the activities of enzymic and non-enzymic antioxidants in rats, Tigriopus japonicus Mori, and goldfish [39][40][41]. Also, our data are consistent with the report that NiSO 4 can decrease the SOD and CAT activities in the liver of mouse [42].…”
Section: Discussionsupporting
confidence: 91%
“…**p < 0.01, compared with the control group or lesions [18][19][20][21][22]. Some studies have reported that NiCl 2 can decrease the activities of enzymic and non-enzymic antioxidants in rats, Tigriopus japonicus Mori, and goldfish [39][40][41]. Also, our data are consistent with the report that NiSO 4 can decrease the SOD and CAT activities in the liver of mouse [42].…”
Section: Discussionsupporting
confidence: 91%
“…MDA, a decompression product of polyunsaturated fatty acids hydroperoxides, is considered as an indicator of ROS accumulation (Dotan et al 2004;Shi and Bao 2007;Wang and Wang 2009). In the present study, PAH stimulates MDA in roots and stems of B. gymnorrhiza, while MDA in leaves seems to be little affected by PAH in a range of concentration applied.…”
Section: Discussionmentioning
confidence: 99%
“…The harpacticoid copepod Tigriopus japonicus has a wide geographical distribution and is regarded as a good model species commonly used in marine ecotoxicological studies (Raisuddin et al, 2007;Wang and Wang, 2010). This copepod is relatively small, the adults being approximately, 1.0 mm generally.…”
Section: Introductionmentioning
confidence: 99%